The Existence of the Indonesian National Police Professional Code of Ethics to Create Law Enforcement Officers with Integrity - Yusri, Yusri; Lewerissa, Yanti Amelia; Leasa, Elias Zadrak (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The dishonorable discharge (PTDH) of seven members of the Indonesian National Police (Polri) who violated the Indonesian National Police's professional code of ethics is a firm action taken by the institution, increasing the awareness of police officers regarding the importance of maintaining discipline and responsibility as law enforcement officers. Compliance with regulations is not only to avoid sanctions but also to build public trust in the police institution.Purposes of the Research: The purpose of this paper is to examine and analyze the factors causing the increase in code of ethics hearings for members of the Indonesian National Police (Polri) who commit crimes and to examine and analyze efforts to realize the Indonesian National Police (Polri) as a law enforcement agency with integrity.Methods of the Research: The research method used is empirical juridical, with primary and secondary data sources. Data collection techniques include observation, interviews, and literature review. Data analysis techniques are qualitative.Findings of the Research: The research results indicate that the factors contributing to the increase in code of ethics hearings for members of the Indonesian National Police (Polri) who commit crimes include: a lack of understanding of the Indonesian National Police Professional Code of Ethics; work pressure; corruption and abuse of power; an organizational culture that does not support ethics; a lack of oversight and accountability; environmental influences; a lack of training and education; and personal motivation. Efforts to realize the Indonesian National Police (Polri) as a law enforcement agency with integrity include: increasing faith and devotion to God Almighty; improving human resources (HR) who uphold the values of integrity in their attitudes and behavior; strengthening internal and external oversight; bureaucratic reform to increase transparency and accountability; and imposing strict sanctions on Polri members who violate the KEPP.